Maternity at Work : a Review of National Legislation - Findings from the ILO's Conditions of Work and Employment Database. - Öun, Ida (International Labour Office, 2005)
Compares the provisions for maternity protection in 166 ILO member States and their conformity with the ILO Maternity Protection Convention, 2000 (No. 183) and its accompanying Recommendation (No. 191). Examines the durations of maternity leave, conditions for paternity, parental and adoption leave, working time, issues of unhealthy work, nursing facilities, etc.